Probiotics for Oral Candidiasis: Critical Appraisal of the Evidence and a Path Forward - Archambault, Linda S.; Dongari-Bagtzoglou, Anna (Frontiers in Oral Health, 2022)
Oropharyngeal Candidiasis (OPC) is a mucosal fungal infection that is prevalent among patients with compromised immunity. The success of probiotics in treating chronic diseases with a microbial etiology component at other mucosal sites (i.e., gastro-intestinal, genitourinary and alveolar mucosae) has inspired research into the use of probiotics in the treatment of OPC. A growing body of research in vitro and in animal models indicates that some probiotic species and strains have inhibitory activities against Candida albicans growth, morphological switching, and biofilm formation. However, recent review and meta-analysis studies reveal a dearth of human randomized, controlled clinical trials on the efficacy of probiotics to treat or prevent OPC, while the majority of these have not based their selection of probiotic strains or the type of administration on sound pre-clinical evidence. In this mini-review, we assess the state of the field, outline some of the difficulties in translating lab results to clinical efficacy, and make recommendations for future research needed in order to move the field forward.